ALTERNATIVE THERAPIES IN REDUCING ANXIETY AND PAIN FOR INVASIVE PROCEDURES IN PEDIATRIC PRACTICE - Smaranda Diaconescu; Magdalena Iorga; Maria Bolat; Raluca Stanca; Gabriela Stefanescu (Romanian Society of Oral Rehabilitation, 2016)
The multiple roles that music plays in our life, entertainment, inspiration, development of cognitive skills and improvement of psychomotor and socio-affective abilities extends to therapeutic effects. The physiological effect of music is reducing the level of stress hormones (cortisol and adrenaline) and releasing endorphins with calming and analgesic properties. An invasive medical procedure such as endoscopy, colonoscopy or surgery is a major factor for distress in children. Dental anxiety with a high prevalence in children has numerous negative effects and a proper management is required; non-pharmacological alternative treatments are studied lately. Many studies concluded that music therapy is useful in reducing nervousness and pain, improving blood pressure, cardiovascular parameters and oxygen saturation and in increasing cooperation and tolerance. Music might be successfully used as a non-invasive, non-pharmacological alternative method with multiple benefits and the potential to reduce major effects of invasive medical procedures in children.